A Novel Prognostic Model Predicts Outcomes in Non-Metastatic Nasopharyngeal Carcinoma Based on Inflammation, Nutrition, and Coagulation Signature - Chen LZ; Li HS; Han GW; Su Y; Lu TZ; Xie HH; Gong XC; Li JG; Xiao Y (Dove Medical Press, 2023)
Li-Zhi Chen,1,2,* Han-Shu Li,1,2,* Gao-Wei Han,1,2,* Yong Su,1,3 Tian-Zhu Lu,1- 3 Hong-Hui Xie,1,3 Xiao-Chang Gong,1,3 Jin-Gao Li,1,3 Yun Xiao1,3 1NHC Key Laboratory of Personalized Diagnosis and Treatment of Nasopharyngeal Carcinoma, Jiangxi Clinical Research Center for Cancer, Jiangxi Cancer Hospital, The Second Affiliated Hospital of Nanchang Medical College, Nanchang, Jiangxi, 330029, People's Republic of China, Nanchang, Jiangxi, 330029, People's Republic of China; 2Jiangxi Medical College, Nanchang University, Nanchang, Jiangxi, 330029, People's Republic of China; 3Department of Radiation Oncology, Jiangxi Clinical Research Center for Cancer, Jiangxi Cancer Hospital, The Second Affiliated Hospital of Nanchang Medical College, Nanchang, Jiangxi, 330029, People's Republic of China*These authors contributed equally to this workCorrespondence: Jin-Gao Li; Yun Xiao, Department of Radiation Oncology, Jiangxi Clinical Research Center for Cancer, Jiangxi Cancer Hospital, The Second Affiliated Hospital of Nanchang Medical College, 519 East Beijing Road, Nanchang, Jiangxi, 330029, People's Republic of China, Tel +86-791-88313632, Fax +86-791-8321742, Email lijingao@hotmail.com; 813898920@qq.comPurpose: This study aimed to assess the prognostic and predictive value of a circulating hematological signature (CHS) and to develop a CHS-based nomogram for predicting prognosis and guiding individualized chemotherapy in non-metastatic nasopharyngeal carcinoma (NPC) patients.Patients and Methods: NPC patients were recruited between January 2014 and December 2017 at the Jiangxi Cancer Hospital. The CHS was constructed based on a series of hematological indicators. The nomogram was developed by CHS and clinical factors.Results: A total of 779 patients were included. Three biomarkers were selected by least absolute shrinkage and selection operator regression, including prognostic nutritional index, albumin-to-fibrinogen ratio, and prealbumin-to-fibrinogen ratio, were used to construct the CHS. The patients in the low-CHS group had better 5-year DMFS and OS than those in the high-CHS group in the training (DMFS: 85.0% vs 56.6%, p< 0.001; OS: 90.3% vs 65.4%, p< 0.001) and validation cohorts (DMFS: 92.3% vs 43.6%, p< 0.001; OS: 92.1% vs 65.5%, p< 0.001). The nomogram_CHS showed better performance than clinical stage in predicting distant metastasis (concordance index: 0.728 vs 0.646). In the low-TRS (total risk scores) group, the patients received RT alone, CCRT and IC plus CCRT had similar 5-year DMFS and OS (p> 0.05). In the middle-TRS group, the patients received RT alone had worse 5-year DMFS (58.7% vs 80.8% vs 90.8%, p=0.002) and OS (75.0% vs 94.1% vs 95.0%, p=0.001) than those received CCRT or IC plus CCRT. In the high-TRS group, the patients received RT alone and CCRT had worse 5-year DMFS (18.6% vs 31.3% vs 81.5%, p< 0.001) and OS (26.9% vs 53.2% vs 88.8%, p< 0.001) than those received IC plus CCRT.Conclusion: The developed nomogram_CHS had satisfactory prognostic accuracy in NPC patients and may individualize risk estimation to facilitate the identification of suitable IC candidates.Keywords: nasopharyngeal carcinoma, circulating hematological signature, induction chemotherapy, distant metastasis-free survival, overall survival